The effectiveness of psychoanalytic psychotherapy in individuals diagnosed with PTSD due to torture and severe human right violations - Özyıldırım, İlker and Baykara, Saliha and Aslantaş Erteki, Banu and Oğlagu, Zerrin and Gürsel, Baran and Akyıl, Deniz and Orhon Baykal, Lale and Yıldırım, Elif and Yıldız, Bilal (Torture Journal, 2023)
Abstract Introduction: Various psychotherapies have been applied to individuals who have been subjected to torture and severe human rights and to patients with PTSD, however, studies assessing the effectiveness of such therapies are limited. Psychoanalytic psychotherapy is said to be used frequently in practice for these patient groups. Yet, there are scarcely any studies assessing its efficacy. In this study, we aim to assess the effectiveness of psychoanalytic psychotherapy in patients with PTSD associated with torture and severe human rights violations. Additionally, the study seeks to monitor the continuity of therapy within the first year and its relationship with overall clinical change. Methods: 70 patients with PTSD related to torture and severe human rights violations who applied to the Human Rights Foundation of Turkey were given psychoanalytic psychotherapy. CGI-S and CGI-I scales were applied to the patients (in Months 1, 3, 6, 9, and 12); and the patients’ continuity of therapy and the changes in their recovery during the one-year psychotherapy period were assessed. Results: 38 (54.3%) of the patients were female. Their mean age was 37.7 years (SD = 12.25), while their mean baseline CGI-S score was 4.67. The mean length of treatment was 21.9 sessions (SD = 20.30). As the number of sessions increased, the final CGI-I scores of the patients improved significantly (p <.001) towards recovery. The change towards recovery became more evident particularly in the patients who had continued the therapy for more than 12 sessions. Mean scores for CGI-I scale were 3.46, 2.95, 2.23, 2.00, and 1.54 for months 1, 3, 6, 9 and 12 respectively. In addition, the drop-out rate was 34% (24 patients) for those who dropped out of therapy prematurely without any CGI-I assessment (9 patients) and those who dropped out of therapy with no improvement in their CGI-I scores –i.e. with CGI-I scores of 4-7 (15 patients). Conclusions: Considering the limited literature in the field, this study has provided significant data on the effectiveness of the use of psychoanalytic psychotherapy in individuals diagnosed with PTSD related to torture and severe human rights violations, despite its limitations –including not involving a control group. Furthermore, the findings might offer important clues regarding the relationship between continuity of therapy and clinical change.